IMPLEMENTASI MANAJEMEN SARANA DAN PRASARANA DI SEKOLAH DASAR : Perencanaan, pengadaan, pengawasan, evaluasi - Dewi Susilo Reni (Institut Agama Islam Ngawi, 2024)
Implementation of Facilities and Infrastructure Management at Kedunggalar 4 State Elementary School is a study that aims to analyze the strategy and implementation of facilities and infrastructure management in the school environment. This research was conducted using a qualitative approach and data collection techniques through observation, interviews and documentation studies. The research results show that the implementation of facilities and infrastructure management in elementary schools has had a positive impact on the student learning environment and educator performance. These findings provide an important contribution to the development of education management at the primary level, as well as providing recommendations for further improvements in efforts to improve the quality of education in primary schools. Keywords: Management, Infrastructure, Elementary School